Modernization Theory Revised: Testing the Relationship between Inward Foreign Direct Investment and Homicide - Levchak, Philip J. (International Journal of Criminology and Sociology, 2024)
Purpose: Modernization theory suggests that economic development is temporarily disruptive to social life and can lead to crimes of violence such as homicide. However, few studies have considered how the modernization process works. Specifically, they neglected the role of globalization. Previous research has suggested that certain measures of globalization may be theoretically linked to homicide. This study examines how inward Foreign Direct Investment (FDI), a key component of globalization and economic development, is associated with cross-national homicide rates. Methods: Data from 101 countries were collected and analyzed to examine the relationship between inward FDI and homicide. Indirect effects of inward FDI on homicide through urbanization and economic growth were also examined. Results: The results show that inward foreign direct investment increases cross-national homicide rates, both directly and indirectly through increased urbanization. Conclusion: While economic development benefits society, the concomitant, deleterious effects should be considered by policymakers, especially those seeking inward foreign direct investment in their countries. Future researchers will want to consider examining other measures of globalization.